Research on the Influence of Air Pollutants and Meteorological Factors on Kawasaki Disease - Yinan Yang; Yanxia Zhang; Fangfang Zheng; Yangbin Guo; Xiaoyan Wang; Huitao Meng; Li Min; Xiaobin Hu (Aerosol and Air Quality Research)
Abstract Purpose Kawasaki disease (KD), an acute systemic vasculitis of unknown etiology, has attracted widespread attention regarding the triggering role of environmental factors in its development. We assessed the effects of air pollutants and meteorological factors on KD, providing evidence for the etiology of KD and data guidance in Northwest China. Methods This time-stratified case-crossover study combined KD inpatient data with air pollutant and meteorological data. We completed individual exposure assessment using ArcGIS 10.8.1 according to the patient’s home address. The associations between air pollutants, meteorological factors, and KD on the previous 0–2 days before disease onset were evaluated through conditional logistic regression. Results We found that each 10 μg m−3 increment of air PM10 at 1-day delay causes a 1.6% increase in the risk of KD (95% CI: 1.001–1.031). PM2.5 was associated with the risk of KD in males at 1-day delay (OR: 1.074, 95% CI: 1.003–1.149). SO2 exposure during the warm season was significantly associated with the risk of KD in children (OR: 1.144, 95% CI: 1.004–1.304). Temperature exposure is associated with the risk of KD, with the maximum effect occurring on the day of onset (OR: 1.060, 95% CI: 1.021–1.101). Conclusion Exposure to particulate matter can increase the risk of KD in children, sex, age and season may modify the effects of particulate matter on KD. In addition, exposure to SO2 during the warm season had a stronger response to KD, and females and patients aged 2–3 and 5 years and above were more sensitive to SO2. Temperature exposure in meteorological factors can significantly increase the risk of KD, with males and patients aged 1–2 years being susceptible group. Graphical Abstract